The role of a single nucleotide polymorphism of the matrix metalloproteinase-1 gene promoter region in invasion and prognosis of meningiomas - Efendioğlu, Mustafa; Başaran, Recep; Bayrak, Ömer Faruk; Işık, Nejat; Kaner, Tuncay; Şahin, Fikrettin; Güçlü, Bülent; Elmacı, İlhan (Turkish Neurosurgical Society, 2014)
AIM:The matrix metalloproteinase (MMP) enzyme family has been shown to be active in tumorigenesis and tumor progression. In this study, we analyzed the prevalence of a guanine insertion in the MMP-1 gene promoter region in meningiomas and its effect on invasion and prognosis. MATERIAL and METHODS: The study was performed with 33 meningioma patients. We also included 33 healthy patients in the study as a control group. The promoter area was amplified by polymerase chain reaction (PCR) following DNA isolation. The polymorphism was detected by restriction fragment length polymorphism (RFLP). RESULTS: According to the WHO classification of meningiomas, 87.9% of the affected patients were grade 1, and 12.1% were grade 2. In total, 72.7% of the meningioma patients (n=24) had at least one copy of the insertion (2G/1G or 2G/2G genotypes) and 27.3% (n=9) did not (1G/1G). There was no significant difference between the meningiorna and control groups according to genotype distribution. CONCLUSION: In this study, the polymorphism in the matrix metalloproteinase-1 gene promoter region did not have an effect on the initiation, growth and progression of meningioma.

AMAÇ: Matriks metalloproteinaz (MMP) enzim ailesinin tümör oluşumu ve progresyonunda etkili olduğu gösterilmiştir. Bu çalışmada menenjiyomlarda matriks metalloproteinaz-1 geni promotor bölgesine guanin insersiyonunun prevalansı ve bunun invazyona ve prognoza etkisi araştırıldı. YÖNTEM ve GEREÇLER: Çalışma 33 tane menenjiyomlu hasta ile yapıldı. Aynı zamanda 33 tane sağlıklı kişi de çalışmaya kontrol grubu olarak dahil edildi. DNA izolasyonundan sonra promotor bölge polimeraz zincir reaksiyonu ile çoğaltıldı. Polimorfizm, restriksiyon fragman uzunluk polimorfizmi ile tesbit edildi. BULGULAR: Dünya Sağlık Örgütü (DSÖ) sınıflamasına göre hastaların %87,9’unda derece I, %12,1’inde derece II menenjiyoma saptandı. Menenjiyomlu hastaların %72,7’si (n=24) en az bir tane guanin insersiyonuna sahipti (2G/1G or 2G/2G genotipleri), ve %27,3’ ü (n=9) sahip değildi (1G/1G). Genotip dağılımına göre menenjiyomlarla kontrol grubu arasında bir fark yoktu. SONUÇ: Bu çalışmada menenjiyomlarda matriks metalloproteinaz-1 geni promotor bölgesindeki polimorfizmin, menenjiyomların başlamasınabüyümesine ve ilerlemesine etki etmediği izlenmiştir.
Menenjiyomlu hastalarda matriks metalloproteinaz-1 geni promotor bölgesi tek nükleotid polimorfizminin invazyon ve prognozdaki rolü
WOS: 000343531700020
PubMed ID: 25269045
Keywords: Meningioma; Single Nucleotide Polymorphism; SNP; MMP-1; Interstitial Collagenase; Matrix Metalloproteinase; Menenjiyom; Tek Nükleotid Polimorfizmi; SNP; MMP-1; Matriks Metalloproteinaz; İnterstisyel Kollajenaz